Social media (FB) : NDA Fragrance / Nur Hashimah Sharani - Sharani, Nur Hashimah (2019)
NDA Fragrance is a business that carries out online business for fragrance products. Fragrance products consist of Inspired Perfume, Body Mist and Body Butter. This business is created to provide an opportunity to all customers who love quality fragrances and want to have them at affordable prices. Apart from selling products to consumers, NDA Fragrance also provides useful info and tips to fragrance customers. Retaining NDA Fragrance's customers is a very strong suit for this business and so we have strategies in place to ensure that our customers remain happy with our products and services. This can be achieved if we employ the best customer service executives who are adept at handling orders, promptly attending to complaints and inquiries. We also intend to provide a listening ear to our clients for feedbacks that will help make the company progress. In addition to reinforcing strategies for maintaining customer loyalty towards NDA Fragrance, expanding and exploring ways to promote this online product and services business in social media is important. Skills and ways to know how to attract customers are important. Start by giving teaser a customer to give the customer a sense of excitement to know which product to sell. Next, the skills to make soft sell to give you an idea of exactly what the product is going to sell in the right way. Last but not least, hard-sell-making skills to customers to attract customers continue to buy promoted products. NDA Fragrance can further enhance this entrepreneurial knowledge to further develop this business in the near future.